Surface physicochemical properties of selected single and mixed cultures of microalgae and cyanobacteria and their relationship with sedimentation kinetics - Joana A. Loureiro (2015)
Background: Microalgae are photosynthetic microorganisms presenting a diversity of biotechnological applications. However, microalgal cultivation systems are not energetically and economically feasible. Possible strategies that can be applied to improve the feasibility of microalgal production include biofouling control in photobioreactors, the use of attached growth systems and bioflocculation. These processes are ruled by surface physicochemical properties. Accordingly, the surface physicochemical properties of Chlorella vulgaris, Pseudokirchneriella subcapitata, Synechocystis salina and Microcystis aeruginosa were determined through contact angle and zeta potential measurements. Additionally, mixed cultures of the selected microorganisms were performed. Sedimentation kinetics of the studied cultures was also evaluated to understand how surface physicochemical properties influence microalgal recovery. Results: All studied microorganisms, except S. salina, presented a hydrophilic surface. The co-culture of S. salina with the other studied microorganisms resulted in a more hydrophobic algal suspension. Regarding zeta potential determinations, all studied suspensions presented a negatively charged surface (approximately -40.8 ± 4.4 mV). Sedimentation experiments have shown that all microalgal suspensions presented low microalgal recovery efficiencies. However, a negative linear relationship between microalgal removal percentage and free energy of hydrophobic interaction was obtained. Conclusions: The evidence of a relationship between microalgal removal percentage and free energy of hydrophobic interaction demonstrates the importance of surface physicochemical properties on microalgal settling. However, the low recovery efficiencies achieved, as well as the high net zeta potential values determined, indicate that another factor to consider in microalgal settling is the ionic strength of the culture medium, which play an important role in suspensions' stability.